Body composition and function in chronic kidney disease - Owen, Paul (2013)
Chronic kidney disease (CKD) is a significant public health issue. The uraemic milieu is associated with profound alterations in body composition and function. Therapeutic interventions to preserve renal function and to provide adequate homeostasis to improve outcomes in all stages of chronic kidney disease may promote other unwanted functional adversities which with careful attention to individualised treatment may be modifiable.